The Effectiveness of Unilateral Cochlear Implantation on Performance-Based and Patient-Reported Outcome Measures in Finnish Recipients - Dietz, Aarno; Heinrich, Antje; Törmäkangas, Timo; Iso-Mustajärvi, Matti; Miettinen, Petrus; Willberg, Tytti; Linder, Pia H. (Frontiers in Neuroscience, 2022)
Understanding speech is essential for adequate social interaction, and its functioning affects health, wellbeing, and quality of life (QoL). Untreated hearing loss is associated with reduced social activity, depression and cognitive decline. Severe and profound hearing loss is routinely rehabilitated with cochlear implantation. The success of treatment is mostly assessed by performance-based outcome measures such as speech perception. The ultimate goal of cochlear implantation, however, is to improve the patient’s QoL. Therefore, patient-reported outcomes measures (PROMs) would be clinically valuable as they assess subjective benefits and overall effectiveness of treatment. The aim of this study was to assess the patient-reported benefits of unilateral cochlear implantation in an unselected Finnish patient cohort of patients with bilateral hearing loss. The study design was a prospective evaluation of 118 patients. The patient cohort was longitudinally followed up with repeated within-subject measurements preoperatively and at 6 and 12 months postoperatively. The main outcome measures were one performance-based speech-in-noise (SiN) test (Finnish Matrix Sentence Test), and two PROMs (Finnish versions of the Speech, Spatial, Qualities of Hearing questionnaire [SSQ] and the Nijmegen Cochlear Implant Questionnaire [NCIQ]). The results showed significant average improvements in SiN scores, from +0.8 dB SNR preoperatively to -3.7 and -3.8 dB SNR at 6 and12 month follow-up respectively. Significant improvements were also found for SSQ and NCIQ scores in all subdomains from the preoperative state to 6 and 12 months after first fitting. No clinically significant improvements were observed in any of the outcome measures between 6 and 12 months. Preoperatively, poor SiN scores were associated with low scoring in several subdomains of the SSQ and NCIQ. Poor preoperative SiN scores and low PROMs scoring were significantly associated with larger postoperative improvements. No significant association was found between SiN scores and PROMs postoperatively. This study demonstrates significant benefits of cochlear implantation in the performance-based and patient-reported outcomes in an unselected patient sample. The lack of association between performance and PROMs scores postoperatively suggests that both capture unique aspects of benefit, highlighting the need to clinically implement PROMs in addition to performance-based measures for a more holistic assessment of treatment benefit.